Impact of tourist-to-tourist interaction on tourism experience: The mediating role of cohesion and intimacy - Lin, Hongxia; Zhang, Meng; Gursoy, Dogan; Fu, Xiaorong (Annals of tourism research, 2019)
Utilizing the Stimulus-Organism-Response paradigm, this study explores how self-disclosure, an important component of tourist-to-tourist interaction, influences tourist experience. Data were collected through a field experiment and analyzed via PLS analysis and PROCESS. Findings indicate that self-disclosure indirectly increases engagement by strengthening perceived cohesion and perceived intimacy. Perceived cohesion and perceived intimacy have indirect effects on satisfaction with experience, through engagement. Further, the initial tie strength moderates the effect of self-disclosure on perceived cohesion and perceived intimacy. These findings contribute to the development of tourism experience research from the perspective of tourist-to-tourist interaction and the social interaction literature by examining the unique interaction mechanism among tourists. •Integrates tourist-to-tourist interaction into tourist experience studies.•Uses PLS analysis to examine data collected by field experiment in China.•Self-disclosure is a significant component of tourist-to-tourist interaction.•Perceived cohesion and intimacy are critical determinants of tourist engagement.•Engagement mediates the impacts of cohesion and intimacy on satisfaction.